Lickometry: a novel and sensitive method for assessing functional deficits in rats after stroke - Ahmed, Jewel; Dwyer, Dominic E.; Farr, Tracy D.; Harrison, David J.; Dunnett, Stephen B.; Trueman, Rebecca C. (SAGE, 2017)
The need for sensitive, easy to administer assessments of long-term functional deficits is crucial in pre-clinical stroke research. In the present study, we introduce lickometry (lick microstructure analysis) as a precise method to assess sensorimotor deficits up to 40 days after middle cerebral artery occlusion in rats. Impairments in drinking efficiency compared to controls, and a compensatory increase in the number of drinking clusters were observed. This highlights the utility of this easy to administer task in assessing subtle, long-term deficits, which could be likened to oral deficits in patients.